Study of distribution of soil moisture in the limits of the drainage basin of wildland with the use of GIS- technologies (Journal of Geography and Environmental Management, 2018)
The article considers the features of soil moisture distribution for arable land in the context of catchment areas. The notion of uniformity coefficient of moisture distribution for a catchment basinis introduced, its influence on localization of soils with temporary waterlogging is determined. A description is given of the algorithm for identifying areas with temporary waterlogging of soils usingGIS technologies. Using the existing digital terrain model using the ArcGIS ArcToolBox toolkit, a GRID model of the slope of the slope of the study site was constructed, and the boundaries of the catchment basins were calculated. Using the “Total drain” tool, lines were constructed that are potential watercourses and form a kind of network within the allocated drainage basins. As a result ofthe performed studies, a method was developed for calculating a completely new uniform moisture distribution coefficient.The advantage of this technique is that to calculate the uniformity of the distributionof moisture, only the data of the digital terrain model of the studied territory is sufficient, and the obtained results of territory classification by the degree of moistening can be attributed to detailed mapping.